A educação na perspectiva espírita no lar Antônio de Pádua: estudo sobre a experiência de adoção - Melo, Rosane Maria Pereira (2013)
How the experience of adoption in the context of spiritist education of the Lar Antônio de Pádua was lived? From this research question, I seek to capture the way it was lived, contextualized in the spiritist education lived in the Lar Antônio de Pádua. In this regard, I discuss the (re) construction of subjects from the lived spiritist education and from the love received by parental figures of adoption, where the institution "bursts" (MANNONI, 1988), and overcomes the segregation (RIZZINI, 2011), opening up to the community and building an informal, social and personal network able to facilitate the inclusion of adopted by the couple Analia Bueno and Fernando Melo, in the social environment of its time. Unveiling the movement to provide love to the subjects, I seek from the situations that led to the children adoption (GUEIROS, 2007; FONSECA, 2006), to the context of adoption, experienced with the couple Analia Bueno and Fernando Melo, who create, from that choice, a powerful work based on the spiritualist praxis, inspired particularly by the reference of the medium and educator Eurípedes Barsanulfo. I unveil how the subjects recomposed themselves from spiritual pain (SAUNDERS, 2005; ELIAS, 2001, 2005), lived (in general) with the original family, by giving meaning to life (FRANKL, 1987). I show, in the new family, how attachment will be gestated (BOWLBY, 1962), the holding (WINNICOTT, 1982), the gestural interaction between mother and baby (SPITZ, 1988), the renewal of the identity matrix (MORENO, 1993) and the reincarnation ambience (BARSANULFO, 2005, 2007, 2011) lived with the couple Anália and Fernando in the context of Lar Antônio de Pádua. The study from the spiritist references is based on Eurípedes Barsanulfo, psychographed by Amui (2000, 2005, 2007, 2011), anchored in Kardec (2002a, 2003a, 2003b, 2002b, 2005, 2007a, 2007b, 2008), Emannuel (1978), Ângelis (1990) by Franco, Bigheto (2006), Incontri (2001, 2006), Linhares (2010a, 2012), Bueno (1992) and Novelino (1985). The Lar Antônio de Pádua has three major educational works, in which a holistic culture moves with the Spiritist ideal, developing the web of life (CAPRA, 1995), moving an affective holonutrition context, constituted by complexus (concept introduced in this thesis from Morin (2007). Methodologically, I’m based at Brandão’s (1984, 2007) participant observation, listening to the life stories of and childhood scenes which are relived through the focus groups. For the analysis and understanding of how the experience of adoption was lived in the context of Spiritist Education at Lar Antônio de Pádua, part of the subjects who were adopted and call themselves sons and daughters of the couple Fernando Melo and Analia Bueno and those who were over fifty-two years engaged in the work ostensibly participated in this research. It was found that Analia and Fernando not only adopted sons and daughters, but built with them a generation, also forming a spiritual family - that is constructed by ties of loveliness, able to overcome the financial and social factors that permeated the birth of the adopted children. It was concluded that educating sons and daughters by Spiritism, inspiring the bonding of adoption, is potent to provide, from love, a psychic and spiritual structure to adopted sons and daughters by this extended family. It was also concluded that the love lived through affective bondage of adoption, with the production of spiritual meaning to life, in this spiritualist matrix in focus, leads to an overshoot of a paradigmatic traditional vision of adoption as a purely biological or social-legal, providing a new emotional and also spiritual approach.